1990
DOI: 10.1016/0735-1097(90)90273-r
|View full text |Cite
|
Sign up to set email alerts
|

The significance of coronery reserve in clinical heart disease

Abstract: The clinical syndrome "coronary insufficiency with normal coronary arteriogram" is found in approximately 10% to 20% of patients with exercise-induced coronary insufficiency. In most of these cases, disturbances of the coronary microcirculation are present. They can appear in vascular diseases (arterial hypertension, systemic immunopathies, immune complex vasculitis), in rheologic diseases (paraproteinemia, hyperlipoproteinemia, polyglobulia) and in disturbances of transport and diffusion of oxygen (carbon mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
19

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(55 citation statements)
references
References 15 publications
1
34
1
19
Order By: Relevance
“…Transient experimental coronary occlusion stimulates myocardial growth (19), and clinical studies have shown increased ventricular mass in patients with coronary stenosis (20). Several studies have reported that CFR was reduced in patients with hypertension, despite the absence of coronary stenosis (6)(7)(8)(9)(10)(11)(12)(13). This pathological alteration has been suggested to cause angina-like chest pain in hypertensive patients without coronary artery disease (21,22), and is regarded as a microvascular disturbance in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient experimental coronary occlusion stimulates myocardial growth (19), and clinical studies have shown increased ventricular mass in patients with coronary stenosis (20). Several studies have reported that CFR was reduced in patients with hypertension, despite the absence of coronary stenosis (6)(7)(8)(9)(10)(11)(12)(13). This pathological alteration has been suggested to cause angina-like chest pain in hypertensive patients without coronary artery disease (21,22), and is regarded as a microvascular disturbance in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Following the initial hypothesis that this phenomenon in patients with hypertensive heart disease is caused by an inadequate blood supply due to impairment of coronary flow reserve (CFR), which is a sort of surrogate marker for coronary microcirculatory disturbance (6), numerous studies have supported the idea that hypertensive patients have reduced CFR (7)(8)(9)(10)(11)(12). However, the mechanisms of the impairment of CFR in hypertensive patients without coronary artery disease remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiologic mechanism is based on diastolic and (later) systolic dysfunction of the left ventricle (21). Moreover, in patients with left ventricular hypertrophy, media hypertrophy of the arterioles is seen, resulting in an increased wall thickness-to-radius ratio (23,24). In consequence, coronary microangiopathy occurs.…”
Section: Atrial Arrhythmias and Arterial Hypertensionmentioning
confidence: 99%
“…In consequence, coronary microangiopathy occurs. Furthermore, the coronary flow reserve is reduced by up to 30% due to disturbances of the microcirculation (resistive vessels) and extravascular myocardial alterations (24)(25)(26). Additionally, interstitial fibrosis and an increased sympathetic tone can participate in the development of cardiac arrhythmias and particularly in the occurrence of atrial fibrillation (27,28).…”
Section: Atrial Arrhythmias and Arterial Hypertensionmentioning
confidence: 99%
“…19 -21 Especially in the presence of additional microvascular disease, [22][23][24] CVR after a successful stent implantation with minimization of the residual stenosis can remain low. This particular aspect may be neglected if CVR rel is applied.…”
Section: Haude Et Al Doppler and Qca Predictors Of Mace After Stentingmentioning
confidence: 99%